Edukasi Pengelolaan Sampah Non Organik Dengan Metode 3R (Reduce, Reuse, Recycle) Bagi Masyarakat Dusun Ngobo - Purwanto, Purwanto; Setyoningrum, Ari Ani Dyah; Sirait, Evi; Nindita, Kirtyana; Santoso, Hero Budi; Alimatussa’diyah, Alimatussa’diyah (EDUPEDIA Publisher, 2024)
Garbage is a severe problem for the community. The waste management that has yet to be carried out optimally is very evident in the community, especially in Ngobo Hamlet, Wringinputih, which is located in Burgas District, Semarang Regency. Residents need to understand waste management thoroughly. It is necessary to educate the community about non-organic waste management with the 3R method (Reduce, reuse, recycle). The purpose of this service activity is for the community to be able to learn about waste problems and the adverse effects of waste, know about the waste selection process, and be able to reduce, reuse, and recycle non-organic waste. The stages in this activity include a literature review, obtaining activity permits coordinated with the cadres of residents of Ngobo Hamlet, planning needs, counseling on waste sorting and handling with the 3R method, and utilizing business opportunities with their potential. This community service program is able to increase community understanding about handling non-organic waste with the 3R method.The reduction method is to reduce the use of excessive materials and energy. Meanwhile, reuse by reusing existing items. While recycling is recycling used goods. In the recycling method, the community is given examples of how to recycle used goods into new goods that have economic value. One example of recycled goods is used gallons, which are recycled into flower vases and trash cans. The changes after this service activity are expected to change community behavior in handling non-organic waste for the better.